Chemical probes and drug leads from advances in synthetic planning and methodology - Gerry, Christopher J.; Schreiber, Stuart L. (Nature reviews. Drug discovery, 2018)
Strategies such as diversity-oriented synthesis aim to explore novel areas of chemical space efficiently by populating small-molecule screening libraries with compounds containing structural features that are typically under-represented in commercially available screening collections. This article highlights how the design and synthesis of such libraries have been enabled by modern synthetic chemistry and illustrates the impact of the resultant chemical probes and drug leads in a wide range of diseases. Screening of small-molecule libraries is a productive method for identifying both chemical probes of disease-related targets and potential starting points for drug discovery. In this article, we focus on strategies such as diversity-oriented synthesis that aim to explore novel areas of chemical space efficiently by populating small-molecule libraries with compounds containing structural features that are typically under-represented in commercially available screening collections. Drawing from more than a decade's worth of examples, we highlight how the design and synthesis of such libraries have been enabled by modern synthetic chemistry, and we illustrate the impact of the resultant chemical probes and drug leads in a wide range of diseases.